2017
DOI: 10.1186/s13063-016-1771-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and nutrition behaviour outcomes of a cluster-randomized controlled trial for adults with metabolic syndrome in Vietnam

Abstract: BackgroundMetabolic syndrome is prevalent among Vietnamese adults, especially those aged 50–65 years. This study evaluated the effectiveness of a 6 month community-based lifestyle intervention to increase physical activity levels and improve dietary behaviours for adults with metabolic syndrome in Vietnam.MethodsTen communes, involving participants aged 50–65 years with metabolic syndrome, were recruited from Hanam province in northern Vietnam. The communes were randomly allocated to either the intervention (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Two studies reported significant positive behaviour change in relation to physical activity in the intervention group [35,41], with one reporting significant increases in moderate intensity activity, walking and total physical activity, and decreased mean sitting time [35]. Six studies reported significant positive behaviour changes related to food intake in the intervention groups [28,31,35,36,38,41].…”
Section: Behaviour Changementioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported significant positive behaviour change in relation to physical activity in the intervention group [35,41], with one reporting significant increases in moderate intensity activity, walking and total physical activity, and decreased mean sitting time [35]. Six studies reported significant positive behaviour changes related to food intake in the intervention groups [28,31,35,36,38,41].…”
Section: Behaviour Changementioning
confidence: 99%
“…Three studies by Straznicky et al [27][28][29] report data from one trial and two studies by Anderssen et al [30,31], as well as the study by Torjesen et al [32] all report data from the Oslo Diet and Exercise Study (ODES) [33]. Two studies by Tran et al [34,35] also report results from the same trial. Data were only included once in any meta-analysis for participant data reported in multiple trials.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations